PENDAMPINGAN PENYUSUNAN VIDEO PEMBELAJARAN MATEMATIKA MELALUI MEDIA SOSIAL TELEGRAM DI MASA PANDEMI CIVID-19 (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
Due to the Covid-19 pandemic, the announcement of an Extraordinary Event (KLB) caused chaos, especially in the field of education, schools were closed, teaching and learning activities in schools were disrupted, learning that was initially carried out face-to-face to be carried out remotely. Teachers are required to prepare teaching materials that are able to support distance learning, therefore it is necessary to provide assistance in the development of learning videos for teachers of mathematics subjects. Of the 190 participants, 120 people collected the work of mentoring products in the form of learning videos that had been made by following the tutorials delivered by adjusting the subject matter that the participants were capable of. Participants stated that the mentoring program that had been implemented was very useful to improve the competence of participants. In addition, participants stated that they would always make learning videos to facilitate learning mathematics at school.